Cellulose Conversion Into Hexitols and Glycols in Water: Recent Advances in Catalyst Development - Manaenkov, Oleg V.; Kislitsa, Olga V.; Matveeva, Valentina G.; Sulman, Ester M.; Sulman, Mikhail G.; Bronstein, Lyudmila M. (Frontiers in Chemistry, 2019)
Conversion of biomass cellulose to value-added chemicals and fuels is one of the most important advances of green chemistry stimulated by needs of industry. Here we discuss modern trends in the development of catalysts for two processes of cellulose conversion: (i) hydrolytic hydrogenation with the formation of hexitols and (ii) hydrogenolysis, leading to glycols. The promising strategies include the use of subcritical water which facilitates hydrolysis, bifunctional catalysts which catalyze not only hydrogenation, but also hydrolysis, retro-aldol condensation, and isomerization, and pretreatment (milling) of cellulose together with catalysts to allow an intimate contact between the reaction components. An important development is the replacement of noble metals in the catalysts with earth-abundant metals, bringing down the catalyst costs and improving the environmental impact.